Plans of possessions of land estates in the 19 c. Lithuania - Girkus, Romualdas; Lukoševičius, Viktoras (Geodesy and Cartography, 2012)
The article gives a scientific overview of the graphical documents of the Vilkmerges pavietas (administrative territorial unit) landed estates in the first half of the 19th century of Lithuania. Specifically it analyses plans of possessions of Pakruojis and Seduva landed estates in Upytes pavietas and plans of possessions of landed estates in Rokiskis county. The article analyses the principle of making the plans and their authorship, orientation, scale, conventional signs, environs, technique they are carried out, and elements of their decoration. It also analyses names of settlements, rivers, woods, bogs and peat bogs that are marked on the maps comparing them with their present-day standardised names. The article concludes that toponyms and hydronyms have essentially preserved the elements of identity. More visible changes are observed in the names of lakes. Article in Lithuanian. XIX a. Lietuvos dvarų valdų planų ypatumai Santrauka. Straipsnyje aptariami XIX a. pirmos pusės Lietuvos Vilkmergės pavieto dvarų valdų grafiniai dokumentai: Upytės pavieto Pakruojo ir Šeduvos dvarų valdų ir Rokiškio grafystės žemės valdų planai. Nagrinėjami planų sudarymo principai, aptariama autorystė, jų kryptingumas, masteliai, sutartiniai ženklai, apimamos teritorijos, gamybos technika, puošybos elementai. Analizuojami planuose pateiktų gyvenviečių, upių, ežerų, miškų, pelkių ir durpynų pavadinimai ir lyginami su nūdienos sunormintais jų pavadinimais. Konstatuojama, kad vietovardžiai ir vandenvardžiai iš esmės išlikę tapatūs. Labiau pakitę kai kurių ežerų vardai. Prasminiai žodžiai: žemės valdos, dvarai, planų sudarymo principai, vietovardžiai, Pakruojis, Šeduva, Rokiškis, Litviniškės. First published online: 03 Aug 2012